Whole Body Vibration Training on Muscle Strength and Brain-Derived Neurotrophic Factor Levels in Elderly Woman With Knee Osteoarthritis: A Randomized Clinical Trial Study - Simão, Adriano Prado; Mendonça, Vanessa Amaral; Avelar, Núbia Carelli Pereira; da Fonseca, Sueli Ferreira; Santos, Jousielle Márcia; de Oliveira, Ana Carolina Coelho; Tossige-Gomes, Rosalina; Ribeiro, Vanessa Gonçalves César; Neves, Camila Danielle Cunha; Balthazar, Cláudio Heitor; Leite, Hércules Ribeiro; Figueiredo, Pedro Henrique Scheidt; et al. (Frontiers in Physiology, 2019)
Background: Osteoarthritis of the knee (kOA) is a chronic, progressive, degenerative health condition that contribute to the imbalance between the synthesis and destruction of articular cartilage. Recently, whole body vibration (WBV) training has been recommended as an effective alternative for strength training in elderly people and various physiological effects are obtained in response to exercise performed on a vibratory platform, such as an increase in muscle activation and improved muscle performance. However, the effects of WBV particularly on the strength of the quadriceps muscle and neuronal plasticity are unknown. Objective: The aim of this study was to evaluate the effects of adding WBV to squat training on the isometric quadriceps muscle strength (IQMS), the plasma levels of brain-derived neurotrophic factor (BDNF) in elderly woman with kOA. Methods: Fifteen elderly women ≥ 65 years of age with kOA were randomized into two interventions: 1) the vibration group (VG), in which participants performed squat exercise training in association with WBV or 2) the exercise group (EG), in which participants performed squat exercise training without vibration, for 12 weeks 3x/week. Results: Compared to the EG group, the VG group demonstrated a significantly greater delta (Δ) in IQMS values (IC95% 0.43 - 7.06; p ≤ 0.05) and in ∆ BDNF plasma levels (IC95% -32.51 to 4217; p ≤ 0.05) after the intervention period. There was an association between increase of ∆ BDNF plasma levels and increase of ∆ IQMS (β = 0.57; R2 = 0.32; p = 0.03). Conclusion: The addition of WBV to squat exercise training improves lower limb muscle performance in elderly women with kOA. These findings suggest that the improvement in muscle performance is related to neuromuscular adaptations induced by WBV.